The Effects of Using Songs to Teach the Subject-Verb Agreement to Low Proficiency L2 Learners - Woo, Mei Wah (2000)
This paper is an exploratory attempt to investigate the effects of using songs with activities and without activities to teach the subject-verb agreement to second language (L2) subjects of low proficiency. This is a qualitative study involving two treatment groups using songs to teach the subject-verb agreement. However, one group will be given the treatment with activities while the other will be given the same treatment without the activities. This study aims to find out if there is any significant difference between the two treatment groups. The subjects of this study are thirty low proficiency Form Four students from a suburban secondary school in Kapar, 16 kilometres from Kelang district. The focus of this study is on the findings of the pre-test, post-test, the lesson plans carried out, and the subjects' responses obtained from the questionnaire given. Observations are also reported from the researcher's anecdotal record and the observer's checklist. The findings of this study reveal that there is no statistical significant difference between the two groups. However, there are descriptive differences and individual improvements made. The reactions obtained from the subjects are positively encouraging although the scores obtained, on the overall, do not reflect these positive responses felt. The findings from this study do not meet expectations anticipated. The researcher hopes that this exploratory attempt can be replicated or improved in future to confirm the claims and findings made in this study. Much more needs to be done to verify the effectiveness of using songs in the Malaysian ESL classroom.